Intracellular Spread of Rabies Virus Is Reduced in the Paralytic Form of Canine Rabies Compared to the Furious Form - Shuangshoti, Shanop (PLoS Negl Trop Dis, 2016)
Studies of the furious and paralytic forms of canine rabies at the early stage of disease have shown a more rapid viral colonization of the cerebral hemispheres in the furious form, as measured by viral antigen within neuronal cell bodies and viral RNA levels. Measurement of cellular processes separate from neuronal cell body provides a visual record of the spread of rabies virus which occurs across synapses. In this study, the amount of rabies viral antigen within cell processes was quantitatively assessed by image analysis in a cohort of naturally rabies infected non-vaccinated dogs (5 furious and 5 paralytic) that were sacrificed shortly after developing illness. Measurements were taken at different levels of the spinal cord, brain stem, and cerebrum. Results were compared to the amount of rabies viral antigen in neuronal cell bodies. Generally, the amount of rabies viral antigen in cell processes decreased in a rostral direction, following the pattern for the amount of rabies viral antigen in neuronal cell bodies and the percentage of involved cell bodies. However, there was a delay in cell process involvement following cell body involvement, consistent with replication occurring in the cell body region and subsequent transport out to cell processes. Greater amounts of antigen were seen in cell processes in dogs with the furious compared to paralytic form, at all anatomic levels examined. This difference was even evident when comparing (1) neurons with similar amounts of antigen, (2) similar percentages of involved neurons, and (3) anatomic levels that showed 100% positive neurons. These findings suggest that intracellular transport of the virus may be slower in the paralytic form, resulting in slower viral propagation. Possible mechanisms might involve host-specific differences in intracellular virus transport. The latter could be cytokine-mediated, since previous studies have documented greater inflammation in the paralytic form.